Penerapan Konsep Entrepreneurship Dalam Pengembangan Usaha Jasa Desain Grafis DESAINKU.ID - Anggi Aulia; Ayu Riski Utami; Bagus Ermus; Ihsan Fadhilah Putra Bahri; Ray Taufik Setiawan; Risma Melati; Sanggri Kesuma Dewi; Syalsa Nabila Yolanda; Harry Pratama Figna (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The development of the digital creative industry has increased the demand for graphic design services. One of the key factors in maintaining sustainability and competitiveness of graphic design service businesses is the application of entrepreneurship concepts. This study aims to analyze the implementation of entrepreneurship concepts in the development of Desainku.id graphic design service business. This research uses a qualitative method with a case study approach. Data collection techniques include interviews, observations, and documentation. The results show that the application of entrepreneurship concepts at Desainku.id is reflected through service innovation, utilization of digital technology, market opportunity orientation, and digital-based marketing strategies. These implementations have a positive impact on increasing the number of clients, market expansion, and business sustainability. This study is expected to serve as a reference for creative service entrepreneurs in developing entrepreneurship-based businesses.